Draft genome sequence of a nitrate-reducing, o-phthalate degrading bacterium, Azoarcus sp. strain PA01T. Issue 1 (December 2015) - Junghare, Madan; Patil, Yogita; Schink, Bernhard
Abstract Azoarcus sp. strain PA01T belongs to the genusAzoarcus, of the familyRhodocyclaceae within the classBetaproteobacteria. It is a facultatively anaerobic, mesophilic, non-motile, Gram-stain negative, non-spore-forming, short rod-shaped bacterium that was isolated from a wastewater treatment plant in Constance, Germany. It is of interest because of its ability to degradeo -phthalate and a wide variety of aromatic compounds with nitrate as an electron acceptor. Elucidation of theo -phthalate degradation pathway may help to improve the treatment of phthalate-containing wastes in the future. Here, we describe the features of this organism, together with the draft genome sequence information and annotation. The draft genome consists of 4 contigs with 3, 908, 301 bp and an overall G + C content of 66.08 %. Out of 3, 712 total genes predicted, 3, 625 genes code for proteins and 87 genes for RNAs. The majority of the protein-encoding genes (83.51 %) were assigned a putative function while those remaining were annotated as hypothetical proteins.